Antony and Cleopatra - Turner, J.,Potter, Nicholas (Macmillan Education UK, 2006)
This Guide provides a critical survey of the responses to this popular play. Chronologically arranged, the book draws on a rich range of critical writings, including Dr Johnson, Coleridge, Bradley and Leavis. This material is linked to more general issues regarding Shakespearean criticism and scholarship, and the development of literary theory. COVER – CONTENTS – NOTE ON THE TEXT – INTRODUCTION: 'Like to a vagabond flag upon a stream': The Vagaries of Opinion Concerning Antony and Cleopatra – CHAPTER ONE: 'Let's do it after the high Roman fashion': Shakespeare's Classical World – CHAPTER TWO: Shakespeare's World Well Lost? Theatre in England during the Interregnum and After – CHAPTER THREE: Dryden's Revision of Antony and Cleopatra – CHAPTER FOUR: Romantics to Victorians: 'This enchanting Queen' – CHAPTER FIVE: Modernists: 'No more but e'en a woman' – CHAPTER SIX: The Editions: 'The varying shore o' the world' – CHAPTER SEVEN: The Romanness of the Roman Plays (1) – CHAPTER EIGHT: The Romanness of the Roman Plays (2) – CHAPTER NINE: Postmodernists: Antony and Cleopatra: 'A child o' the time'? – CONCLUSION: 'Infinite variety'? – NOTES – SELECT BIBLIOGRAPHY – INDEX – A – B – C – D – E – F – G – H – I – J – K – L – M – N – O – P – Q – R – S – T – U – V – W – X.
Description based on publisher supplied metadata and other sources
Keywords: Antonius; Marcus - In literature; Electronic books